Analysis of Profitability on Stock Prices: Capital Structure as a Mediator, Firm Size as a Control: Analysis of Profitability on Stock Prices: Capital Structure as a Mediator, Firm Size as a Control - Wawan Ichwanudin; Seandy Ginanjar (Jurnal Ecoment Global, 2026)
Objective: This study aims to empirically investigate the role of the Debt-to-Equity Ratio (DER) as a mediating factor between Return on Assets (ROA) and stock prices in food and beverage companies listed on the Indonesia Stock Exchange (IDX). It seeks to expand existing knowledge by analyzing the connections between these financial metrics and stock prices, offering valuable insights into corporate financial performance and its influence on market valuations. Design/Methods/Approach: Using regression analysis, the study tests the mediation of DER in the relationship between ROA and stock prices. The sample consists of firms in the food and beverage industry listed on the IDX. The hypotheses are tested through regression models to examine both direct and indirect effects. Findings: The results show that DER does not significantly affect ROA or stock prices. While ROA still significantly influences stock prices when DER is included as a mediating variable, DER itself does not mediate the relationship. This suggests that investors focus more on profitability (ROA) when making decisions, rather than considering DER. Originality/Value: This research introduces a novel perspective by exploring DER's mediating role, challenging the traditional view of its significance in investment decisions within the Indonesian food and beverage sector. Practical/Policy implication: Investors should focus on profitability (ROA) directly, rather than DER, when evaluating stock prices. This approach can help refine financial analysis models and investment strategies,